Analysis of microstructure, mechanical properties, wear characteristics and corrosion behavior of SLM-NiTi under different process parameters. (March 2022) - Yu, Zhenglei; Xu, Zezhou; Guo, Yunting; Sha, Pengwei; Liu, Ruiyao; Xin, Renlong; Li, Lunxiang; Chen, Lixin; Wang, Xiebin; Zhang, Zhihui; Ren, Luquan
Abstract: In this paper, the NiTi alloy is prepared by selective laser melting (SLM), and the influence of different process parameters on the microstructure, mechanical properties, corrosion and friction is compared and analyzed. The results of XRD, DSC and EDS showed that the sample prepared with high power and high scanning speed (HP) tends to form the B2NiTi phase, while the sample prepared with low power and low scanning speed (LP) tends to form the B19′NiTi phase. The electrochemical test, friction and wear experiments and tribocorrosion tests showed the LP sample had better corrosion resistance whether in simulated body fluids (SBF) or 3.5 wt% NaCl solution, while the HP exhibited better wear resistance and tribocorrosion resistance. The influence mechanism of different process parameters on the corrosion resistance and wear resistance of the samples is discussed in detail in this paper. Highlights: The microstructures and phase compositions of SLM-NiTi under different parameters present distinct difference. The friction behavior and corrosion resistance of SLM-NiTi under different parameters are reported firstly. The tribocorrosion behavior of SLM-NiTi under different parameters is different from that of friction or corrosion alone.